EARLY WARNING SYSTEM OF STUDENT HEALTH CONDITIONS THROUGH HEART RATE AND BODY TEMPERATURE MEASUREMENT USING MLX90614 SENSOR, MAX30100 SENSOR AND SMS GATEWAY AT SMAN 6 CIMAHI - Dwiyanti, Tantri; Astriany Rizky, Ardelia (INFOKOM (Informatika & Komputer), 2025)
As awareness of the importance of health in supporting effective learning processes at school increases, a physical condition monitoring system becomes crucial. This research aims to design and implement an early warning system capable of proactively monitoring students’ health conditions. The system integrates a MAX30100 sensor to measure heart rate and blood oxygen saturation (SpO2), and an MLX90614 sensor for non-contact body temperature measurement. Data from both sensors will be processed by a microcontroller to identify anomalies. If one or more of a student’s health parameters are detected to be outside the predetermined normal range, the system will automatically send a notification containing the student’s health data via an SMS Gateway to school authorities, such as homeroom teachers. This mechanism ensures a quick response to students’ health issues within the school environment. The test results show that this early warning system is effective and reliable for accurately monitoring health. The implementation of this system is expected to improve the effectiveness of health monitoring in schools and provide a sense of security to parents.